Development of Writing Teaching Materials with a Contextual Approach of Public Junior High School (SMPN 1), Pinang City, South Labuhan Batu, Indonesia - Dewi Wahyuni; Risnawaty Risnawaty; Sutikno Sutikno; Rahmat Kartolo (International Journal of Research in Community Services, 2022)
Based on observations from interviews with Indonesian language and literature teachers at SMPN 1, Pinang City, South Labuhan Batu, Indonesia, it is known that students' writing skills still need to be improved. Only 60% of students who are able to write instructions properly and correctly, the rest still have difficulty in writing instructions. In this study, there are two categories of research data sources. First, the data source for the prototype needs of teaching materials consists of students and teachers. Second, the prototype validation data source that will assess the prototype of teaching materials writing instructions with a contextual approach. Sources of data needs prototype teaching materials in this study are students and teachers. Sources of prototype validation data that assess the product development of this research are teachers and expert lecturers. The main finding of this study is the average value given by three teachers and two experts on the prototype of teaching materials for writing instructions with a contextual approach, namely (1) aspects of material presentation of 69.79 included in the good category, (2) aspects of content /material of 79.17 is included in the good category, and (3) aspects of language and readability of 80.42 are included in the good category. After making improvements based on the results of assessments and suggestions by teachers and experts, the teaching materials write instructions with the Contextual after repair contains material on the meaning of writing instructions, characteristics that need to be considered in writing instructions, steps for writing instructions, examples of writing instructions, and effective sentences.